To Determine the Effect of Prothrombin Time (PT), Activated Partial Thrombopalstin Time (APTT), and International Normalized Ratio (INR) Levels on Gender and Age - Aysha Sultana, Fida Hussain, Razia Asif, Amanullah Bhutto, Shabnam, Azhar Ali, Kiran Aamir, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatic function, coagulation disorders, and the risk of postoperative bleeding can all be detected with PT assay. When it comes to measuring "extrinsic route" coagulation factors, the PT is the most commonly used test. It is possible to check for a lack of intrinsic or common route factors by measuring the duration to trigger partial thromboplastin (aPTT). A solution to the problem of inconsistent PT measurements among laboratories was the creation of the International Normalized Ratio (INR). Laboratory-specific reference intervals can have a significant impact on the quality of patient treatment by influencing clinical decision-making. Objective: The purpose of this study is to determine if gender and age affect PT, International normalised ratio (INR), and aPTT levels in people without known liver disease or anticoagulant therapy. Method: Between July and December of 2021, patients without a past history of bleeding were admitted to the LUMHS Hyderabad civil hospital for minor surgical procedures (inguinal/umbilical hernia repair, caesarean section, rectal polyp excision, and diagnostic cystoscopy). There were 2274 patients in all, with 766 males and 1508 females. According to their chronological age, patients were separated into three groups. The study sampled 268 men and 22 women aged 0-14, 222 men and 1335 women aged 15-50, and 151 women and 276 men in the third age range (over the age of 50 year). Systemex CA-500 auto analyzer was used to conduct the analyses. Results: Males and females have considerably different PT and INR values. Men and women between the ages of 15 and 50 were more likely to have increased PT, INR, and aPTT readings than those between the ages of 0 and 14. Males and females between the ages of zero and fourteen had the lowest aPTT levels. Between the ages of 15 and 50, women and men had higher PT, INR, and aPTT values than women and men over 50. PT, INR, and aPTT reference values based on a 95% confidence interval for men and women, as well as sexes and ages. Conclusion: In this arena, a dearth of study has established that gender and age have little effect on PT, INR, and aPTT levels. Gender and age disparities in clinically used reference ranges for PT, INR, and aPTT must be taken into account. Keywords: Prothrombin Time, INR, APTT, Outcomes